Tschechische Republik/Czech Republic - Válková, Helena (Untersuchungshaft und Untersuchungshaftvollzug ; 2, 1994)
The Czech and Slovak Republics were formally separated from each other at the beginning of 1993. Many of the laws dicussed in this paper were previously federal (Czechoslovakian) laws, though many other matters - for example prison legislation - were matters for national (that is, Czech or Slovakian) competence. Despite the separation of the two states, the old (federal, Czechoslovakian) laws have for the most part remained in force. However, with the development of new national laws - discussed in this paper with regard to the Czech Republic - the two criminal justice systems, which were in most respects very similar, may now begin to diverge from each other in significant ways. This paper, though originally written prior to the separation of the to states, has been amended to concentrate specifically on the situation in the Czech Republic.